The Meaning of Rejang Pingit Dance Performance at Geriana Kangin Village, Karangasem, Bali in the Global Era - Ruastiti, Ni Made (Humaniora: Journal of Indonesia Culture and Society, 2018)
This research was compiled from the research results that aimed to understand the meaning of RejangÂ Pingit dance performance in the global era. This research was conducted because of the imbalance betweenÂ assumptions and reality in real life. The people who lived in the global era should be more interesting withÂ beautiful performances that were simply performed. However, the fact was different. Although Rejang PingitÂ dance was very simple, people of Geriana Kangin village preserved it. The question was what was the form ofÂ the Rejang Pingit dance performance, what was the meaning contained in the performance? This research usedÂ the qualitative method. The data sources of this research were Pingit Rejang dance performance, relatedÂ informants, journals, and previous research results. All data that had been collected were analyzed usingÂ aesthetic theory, religious theory, and the theory of power relations. The results show that Rejang Pingit danceÂ is performed in the form of dance off (with no play). It can be seen from the way of presentation, choreography,Â performance structure, dressing, makeup, and musical accompaniment of the performance. People of GerianaÂ Kangin village continue to preserve Rejang Pingit dance because it is considered to have the meaning ofÂ aesthetic, religious, social, and cultural. Their belief in the myth of the essence of life that undergoes the RejangÂ Pingit dance is so strong so that they still preserve the dance up to now. Â